The Potential of Ecological Farming in Delivering Social and Economic Development to Small Holder Farming Families (The Rwenzori Experience) - Tibasiima, Thaddeo; Dissing, Inge Lis; Dissing, Aage; Nalunga, Jane; Isgren, Ellinor; Masereka, Longino (Proceedings of the Scientific Track, 2016)
Since 2009 collaboration between Sustainable Agriculture Trainers’ Network (SATNET), National Organic Agriculture Movement of Uganda (NOGAMU) and Organic Denmark (OD) has seen the establishment of over 130 ecological Farmer Family Learning Groups (FFLGs) in the Rwenzori region. An FFLG is a group of 15-30 small holder farmers who get together motivated to improve their livelihoods through ecological farming alternatives made possible through learning and acting together practically on the farm. The practical learning is done in rotation such that every farmer’s farm is uniquely studied to provide for the variations from one farm to another. In every FFLG, learning is guided by a Community Process Facilitator (CPF). A CPF is a person knowledgeable and experienced in ecological farming and has innovative skills to steer the group through from one stage of development to another. A typical FFLG therefore is characterized by learning with and from each other about ecological/good traditional farming methods, working on the farm of each member as a group, savings and credit schemes, joint marketing of produce and taking social responsibility such as opening a community village road, maintaining a water scheme, paying school fees and scholastics for orphans, constructing a pit latrine for a widow to mention a few. (See also, Mette et al., 2012) The Rwenzori region of Uganda is a mountainous area, highly populated, endowed with relatively naturally fertile alluvial soils that are inherently capable of giving life to a diversity of crops and animals.